“A therapy agreement” between a bilingual speech therapist and a bilingual child: their interaction in the perspective of conversation and thematic analysis - Młyński, Rafał (Papers in Linguistics, 2025)
In literature of the subject, the issue discussed in the article is associated with the concept of clinical discourse. The study examines, among other matters, conversations between speech therapists and their patients/clients conducted mainly during therapeutic procedures. The focus is on ‘small talk’ conversations. They include linguistic ways of creating a therapeutic bond, i.e. a relationship between the speech therapist and the patient/client based on understanding and trust. The presented study also addresses this issue as seen from the perspective of conversations before and during speech therapy diagnosis. The study involved bilingual people, i.e. a Polish-American speech therapist and children from the Polish diaspora. Their conversations were scrutinised using conversation and thematic analysis. The use of these methodologies helped to demonstrate micro-strategies and conversation topics that occurred during the speech therapist’s conversations with the children. The influence of bilingualism on the contact between them was also considered.